Indoor environmental quality to ensure the health and wellbeing of vulnerable people in residential buildings: a systematic review - Hernandez-Martin, Mar; Del Ama Gonzalo, Fernando; González-Lezcano, Roberto Alonso (Frontiers in Built Environment, 2025)
Indoor environmental quality (IEQ) is an essential topic nowadays due to its direct impact on occupant health and wellbeing. Most research, however, has focused on commercial and workspace typologies, leaving residential buildings underexplored. Importantly, the effects of IEQ are not experienced uniformly across all populations. Age-related changes and cognitive function, in particular, significantly influence how occupants experience indoor environments. This makes infants and older adults and/or with disabilities especially vulnerable. Understanding these parameters is crucial to designing comfortable, healthy, and inclusive buildings for all user profiles. This review aimed to document research on IEQ, particularly concerning vulnerable populations in residential building typologies. The findings revealed how different vulnerable groups (children, elderly people, pregnant women, and people with disabilities) are affected by the main IEQ domains (thermal, air quality, lighting, acoustics). On the one hand, this relationship is essential for adopting healthy habits when using buildings as users, and on the other, for methods, factors, and strategies to consider and apply when designing healthy and inclusive buildings as architects, designers, and engineers. The quality of the indoor environment must be considered throughout the entire life cycle of a building, from decisions in the initial design stages to its maintenance.